Ethical issues in participatory arts methods for young people with adverse childhood experiences - Pavarini, G; Smith, LM; Shaughnessy, N; Mankee-Williams, A; Thirumalai, JK; Russell, N; Bhui, K (Wiley, 2021)
Context Participatory arts-based methods such as photovoice, drama and music have increasingly been used to engage young people who are exposed to psychosocial risks. These methods have the potential to empower youth and provide them with an accessible and welcoming environment to express and manage difficult feelings and experiences. These effects are, however, dependent on the way these methods are implemented and how potential ethical concerns are handled.